Syntheses of 2,3-dioxopyrrolidines with anisaldehyde using different amines / Norhabibah Mohamad - Mohamad, Norhabibah (2009)
2,3-dioxopyrrolidines were synthesized using anisaldehyde with different amines in a suspension of sodium diethyl oxalacetate (1 equiv), amine (1 equiv) and anisaldehyde (1 equiv) in ethanol. Three different amines were used and they were methylamine, benzylamine and isopropylamine. Many possibilities of syntheses products of 2,3- Dioxopyrrolidines were investigated. 2,3-Dioxopyrrolidines obtained were in moderate yields but of high purity. A significant advantage of these products was that most of them can be crystallized out of the reaction mixture. The synthesized compounds can lead towards the syntheses of biologically active natural products. The compounds were also reduced using zinc powder in the presence of acid. Reduction of synthesized 2,3- Dioxopyrrolidines gave the corresponding secondary alcohols.